Design, architecture and the value to tourism. Issue 5 (August 2019) - Scerri, Moira; Edwards, Deborah; Foley, Carmel
Architecture has been recognized for its supporting role in the enhancement of the physical assets of destinations, which play a leading role in drawing tourists who identify and associate destinations with these architectural landmarks. While generating tourist expenditure is not the aim of most architects, many are increasingly aware that articulated and functional buildings become visitor attractions in their own right – an externality that requires valuing. However, the value assigned to iconic architecture is often restricted to the bricks and mortar construction, and the broader contributions a building can deliver to its stakeholders are largely ignored. This article explores the capacity for architecture to attract tourists and effect direct tourism spend through the examination of five cases, each of which has attempted to estimate their economic value to tourism. This article proposes a model for estimating the future value of iconic buildings and tests its application to the University of Technology Sydney, Gehry-designed, Dr Chau Chak Wing building. The implications of the framework and future research are discussed.